The Heart’s Secret Bridge: Ruptured Sinus of Valsalva Aneurysm Masquerading as a Gerbode Defect - Khalid Sawalha; Angel Lopez-Candales (Heart Views)
Our case presents a 53-year-old male with type 2 diabetes and dyslipidemia presenting to the emergency department with symptoms of chest pressure, palpitations, dyspnea, and exercise intolerance. On initial imaging, an abnormal color flow signal was seen that was initially thought to be secondary to a Gerbode defect. However, using more detailed imaging, cardiac computed tomography angiography suggested the possibility of a noncoronary sinus of Valsalva aneurysm (SOVA) rupture into the right atrium, making the diagnosis challenging. Finally, transesophageal echocardiography confirmed rupture of a SOVA. This case report highlights the importance of maintaining a high index of suspicion when considering rare cardiac anomalies and emphasizes the significance of using different imaging modalities to reach an accurate diagnosis.